Moisture Control in Your Home, Part 2: Room by Room Tips - Hyun-Jeong Lee; Virginia Peart (EDIS)
FCS3257, a 3-page fact sheet by Hyun-Jeong Lee and Virginia Peart, gives detailed, practical tips on how to control and prevent moisture problems in each room in the house, thereby preventing the growth of mold and mildew. This publication combines, updates, and supersedes FCS3042, FCS3211, FCS3212, FCS3213, FCS3239, and FCS3245. Published by the UF Department of Family, Youth and Community Sciences, January 2007.